2008
DOI: 10.1055/s-2008-1067026
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Arylsulfonamides and Azetidine-2,4-diones via Multicomponent Reaction of an Amine, an Acetylenic Compound, and an Arylsulfonyl Isocyanate

Abstract: An effective route to novel arylsulfonamides is described. It involves the reaction of an enamine derived from the addition of primary or secondary amines to acetylenecarboxylates (dialkyl acetylenedicarboxylates or alkyl propiolates) with an arylsulfonyl isocyanate. These arylsulfonamides show dynamic NMR behavior in solution. A different reactivity pattern was observed with the methyl 3-(diethylamino)acrylate. The latter, generated in situ from Et 2 NH and methyl propiolate, on reaction with an arylsulfonyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Finally, we examined the enamine derived from methyl propiolate ( 1c ) (Scheme ) and found that it reacted with 3a to afford 2,4-dienal 9 in 52% yield. Noteworthy is the fact that 2,4-dienals are useful conjugated carbonyl compounds in organic synthesis …”
Section: Resultsmentioning
confidence: 99%
“…Finally, we examined the enamine derived from methyl propiolate ( 1c ) (Scheme ) and found that it reacted with 3a to afford 2,4-dienal 9 in 52% yield. Noteworthy is the fact that 2,4-dienals are useful conjugated carbonyl compounds in organic synthesis …”
Section: Resultsmentioning
confidence: 99%
“…With this nascent SAR, the authors proceeded to further explore substitution effects on the benzyl group, determining that 2,6-dichloro and 2,6-difluoro substitutions were favorable for activity. Thiobenzylated analogs (6)(7)(8)(9)(10)(11)(14)(15)(16)(17)(18)(19) exhibited submicromolar potency in both enzyme and cell-based (NL4-3 cells) assays. Substitution studies on the aromatic unit of the S-benzyl moiety (R 4 ) indicated that para-substitution was highly beneficial to activity regardless of the electronic nature of the substituent (e.g., 6-8, 4-OMe, 4-CN, 4-NO 2 ; ID 50 ) 0.032, 0.1, 0.075 µM, respectively).…”
Section: (Fluorous)mentioning
confidence: 99%
“…22,23 In recent years some interesting research based on using isoquinoline derivatives and activated acetylenes in the presence of compounds containing acidic hydrogen, with analogous transformations have been reported. [29][30][31][32][33][34] In this communication as part of our continuing effort into the design of new routes for the preparation of biologically active heterocyclic compounds [24][25][26][27][28] using the synthesis and reactions of activated acetylenes and isoquinoline in the presence of 2-aminobenzothiazole. Herein we describe a simple, one-pot, three-component synthesis of dihydroimidazo [2,1-a]isoquinolines and dihydroimidazo[2,1-a] quinolines.…”
Section: Introductionmentioning
confidence: 99%